Longitudinal analysis of Voice Handicap Index in early glottic cancer patients treated with transoral laser microsurgery: age, gender, stage and time dependence. Issue 4 (29th March 2019) - Lane, C; Rigby, M; Hart, R; Trites, J; Levi, E; Taylor, S M
Abstract: Objectives: Transoral laser microsurgery is an increasingly common treatment modality for glottic carcinoma. This study aimed to determine the effect of age, gender, stage and time on voice-related quality of life using the Voice Handicap Index-10. Methods: Primary early glottic carcinoma patients treated with transoral laser microsurgery were included in the study. Self-reported Voice Handicap Index testing was completed pre-operatively, three months post-operatively, and yearly at follow-up appointments. Results: Voice Handicap Index improvement was found to be dependent on age and tumour stage, while no significant differences were found in Voice Handicap Index for gender. Voice Handicap Index score was significantly improved at 12 months and 24 months. Time versus Voice Handicap Index modelling revealed a preference for non-linear over linear regression. Conclusion: Age and stage are important factors, as younger patients with more advanced tumours show greater voice improvement post-operatively. Patient's Voice Handicap Index is predicted to have 95 per cent of maximal improvement by 5.5 months post-operatively.